Nuclear maturation and structural components of nonhuman primate cumulus-oocyte complexes during in vivo and in vitro maturation - Nyholt de Prada, Jenna K. (2008)
STUDY OBJECTIVE: To compare cumulus cell structure and timing of oocyte maturation of in vitro and in vivo matured nonhuman primate oocytes. DESIGN: In vivo (VVM) and in vitro (IVM) maturation of oocytes. SETTING: Animal cell culture laboratory. ANIMAL(S): 48 female rhesus macaques. INTERVENTIONS: 15 females were administered FSH and aspirated oocytes were cultured in vitro for 0, 3, 6, 12 or 24 hours (IVM). 33 females were administered FSH and hCG and oocytes were collected 3, 6, 12, or 28–30 hours following hCG (VVM). MAIN OUTCOME MEASURES: Nuclear maturation and microtubule scores of oocytes and actin and tubulin transzonal processes of cumulus cells. Embryo development was observed for VVM oocytes. RESULTS: The rate of nuclear maturation was faster for IVM oocytes compared to VVM oocytes. Actin transzonal processes decreased 0 to 12 hours post hCG for VVM oocytes. Tubulin transzonal processes of IVM and VVM oocytes decreased from 0 to 24 hours and 0 to 3 hours respectively. Embryo development improved as VVM time increased. CONCLUSIONS: Nuclear maturation and remodeling of cumulus oocyte complex structural components associated with IVM do not parallel that of oocyte maturation in vivo, indicating that in vitro culture conditions continue to be sub-optimal.